Effectiveness of medical therapy for treatment of idiopathic frequent premature ventricular complexes. (7th July 2021) - Tang, Jacky K. K.; Andrade, Jason G.; Hawkins, Nathaniel M.; Laksman, Zachary W.; Krahn, Andrew D.; Bennett, Matthew T.; Heilbron, Brett; Chakrabarti, Santabhanu; Yeung‐Lai‐Wah, John A.; Deyell, Marc W.
Abstract: Introduction: The relative effectiveness of medical therapy compared with a conservative approach of monitoring in patients with idiopathic frequent premature ventricular complexes (PVCs) is uncertain. We evaluated the effectiveness of medical versus conservative therapy for frequent PVCs. Methods: Patients with frequent PVCs (≥5%) were prospectively enrolled in this cohort study between 2016 and 2020. In patients with normal cardiac function and no structural heart disease, those receiving medical therapy were compared with controls without therapy. Patients were followed longitudinally for change in PVC burden and with serial echocardiography. Results: Overall, 120 patients met inclusion criteria (mean: 56.5 ± 14.6 years, 54.2% female) with 53 on beta‐blockers or calcium channel blockers (BBs/CCBs), 27 on Class I or III antiarrhythmic drugs (AADs), and 40 patients treated conservatively. Median initial PVC burden ranged from 15.5% to 20.6%. The median relative reduction of PVCs was 32.7%, 30.5%, and 81.3%, in the conservative therapy, BBs/CCBs, and AADs cohorts, respectively. AADs had greater PVC reduction compared with BBs/CCBs ( p = 0.017) and conservative therapy ( p = 0.045). PVC reduction to <1% was comparable across groups at 35.0%, 17.0%, 33.3%, respectively. Four patients (4/120, 3.3%) developed left ventricular dysfunction. Rates of adverse drug reactions and medication discontinuation were similar between groups, with no serious adverse events noted. Conclusion: In patients with idiopathic frequent PVCs, BB, and CCB have limited effectiveness in PVC reduction. Class I and III AADs have superior effectiveness for medical therapy in symptomatic patients, but only achieved complete PVC resolution suppression in one‐third of patients.